2006
DOI: 10.1002/app.23367
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization and characterization of 2‐hydroxyethyl methacrylate onto jute fiber by photoirradiation

Abstract: UV radiation induced graft copolymerization of 2-hydroxyethyl methacrylate onto natural lignocellulose (jute) fiber was carried out by two methods: simultaneous irradiation and grafting and preirradiation grafting. 1-Hydroxycyclohexyl-phenylketone was used as the photoinitiator in both methods. In the former method, the variation of the graft weight was measured for different values of radiation exposure time and the concentrations of both the monomer and photoinitiator. The latter method produced up to 76% gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…However, the inevitable and uncontrollable homopolymer formation is still too high [25], which reduces the grafting efficiency, requires a complex postgrafting process, and generates a large amount of raw material waste. An alternative to the simultaneous irradiation and grafting method is the preirradiation method [26]. The preirradiation method causes little homopolymerization reaction [27], and requires a relatively simple postgrafting process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inevitable and uncontrollable homopolymer formation is still too high [25], which reduces the grafting efficiency, requires a complex postgrafting process, and generates a large amount of raw material waste. An alternative to the simultaneous irradiation and grafting method is the preirradiation method [26]. The preirradiation method causes little homopolymerization reaction [27], and requires a relatively simple postgrafting process.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-assisted grafting, which generates surface functionality on the fibers tailored to encourage chemical bonding and crosslinking at the polymer interface, may utilize UV light, 105,108,111,[115][116][117]141 electron beam, 122 gamma rays, 102,139,140,142,143 and even microwave radiation. 144 Nonionizing UV light and microwave radiation, owing to their comparatively lower energies, are not as effective as ionizing radiation.…”
Section: Surface Modification Alternativesmentioning
confidence: 99%
“…Earlier studies onto photo-induced grafting onto cellulose have already shown its feasibility (Mohanty and Singh 1988), but most of them deal with cotton and jute, grafting common acrylic monomers such as methyl methacrylate or 2-hydroxyethyl methacrylate monomer, in order to improve tensile strength (Khan et al 2004a, b;Khan and Ahmad 2006;Ghosh and Paul 1983;Kubota and Kuwabara 1997;Shukla and Athalye 1995;Shukla and Athalye 1993;Rahman 2009). Similar structures were also used for paper conservation purposes (Margutti et al 2001;Princi et al 2005).…”
Section: Introductionmentioning
confidence: 98%